SUSTAINABILITY INDEX ASSESSMENT OF URBAN TRANSPORT SERVICES IN DEVELOPING CITIES - Prayudyanto, Muhammad Nanang (ASTONJADRO, 2021)
The growth and concentration of motor vehicles in developing cities has led to increased demand for urban mobility. Renewed commitments of Asian cities are required in order to achieve the SDG target on urban mobility as well as to enhance overall sustainability of urban transport systems and services. Cities and countries need to track the progress in improving urban mobility. With a view to support evidence based decision, the paper introduces the Sustainable Urban Transport Index (SUTI) of urban transport services, to help summarize, track and compare the state of urban mobility in Asian cities, as model for developing cities in the world. It also presents the results of pilot application of SUTI in four Asian cities: Greater Jakarta; Kathmandu; Hanoi; and Colombo. The four pilot cities were able to collect data, analyzed and assess the state of urban mobility in their city using SUTI. The assessment result supported policy makers to identify policy gaps, prioritize additional measures and investment strategies required to improve urban transport systems and services in each city. The visual output display in spider diagram was useful to comprehend state of all 10 key indicators in a glace. The pilot study demonstrated the usefulness of SUTI tool and the pilot cities were already using the results of SUTI analysis. In Kathmandu additional efforts are required to improve pedestrian infrastructure and facilities, Colombo needed to improve quality and reliability of public transport system, while Hanoi and Greater Jakarta need to put additional efforts to increase mode share of public transport system.